A study on the preference of dentist attire among pre-schoolers in Central District, Diliman, Quezon City - Lagasca, Annabelle
The study was aimed to determine whether there is a significant difference in the preference for dentist attire between pre-school children with dental experience and those without in Central District, Diliman Quezon City. Subjects were chosen from pres-schoolers aged three to six years old, with no mental deficiency, can identify basic colors and whose parents are not dentist. Photographs of a model with three different attires (informal, formal, fancy type) were shown and asked to choose one. Data gathered was statistically analyzed with the Chi-square test and through percentages distribution. Results show to significant difference in the preference of attire between with and without dental experience. A greater percentage (42.9%) prefered the formal attire, while 30.2% chose the informal attire and the clown costume was least prefered (26.9%).